Logics of Educational Stratification: A Cross-National Map of Educational Inequality. (26th March 2012) - Schlicht-Schmälzle, Raphaela; Ackermann, Kathrin
Abstract : Equality of education is often seen as the fundament of the overall equality of opportunity in modern societies. However, no reliable and comprehensive cross-national comparison of educational inequality hitherto exists. The aim of the present paper is to provide a cross-national comparative outline of diverse dimensions of educational inequality in the OECD world. We estimate the effects of three highly influential aspects of socioeconomic background on educational achievement in each OECD country in order to create a ranking of educational inequality in 30 capitalist countries. The central finding is that we indeed cannot identify a single cross-national ranking but three dimensions of education inequality: educational inequality based on economic, educational, and migration background at home. Capitalist economies thus do not only differ with regard to the degree of inequality but, first and foremost concerning the predominant patterns of inequality and the main distributive keys.